Choreography of Disobedience: Beckett's Endgame. Issue 2 (September 2014) - Gatti, Luciano
<x xml:space="preserve">Abstract</x> The article discusses Beckett's staging of Endgame at the Schiller Theater in Berlin in 1967. The starting point is the debate between the reassertion of the autonomy of drama, proposed by Christoph Menke's theory of tragedy, and Hans-Thies Lehmann's theory of post-dramatic theatre. The article argues that neither of these positions provides a proper understanding of Beckett's work as a theatre director because his stagings demand the analysis both of the stage materiality, which does not appear in studies on the autonomy of drama, as the elements of epic and dramatic genres, which are hardly discussed by the theory of post-dramatic theatre. The article seeks to demonstrate that Beckett's work as a theatre director, besides its relevance to Beckett's studies, has much to contribute to the debate on contemporary theatre.